Evaluation of a battery energy storage system in hospitals for arbitrage and ancillary services. (November 2021) - Mustafa, Motasem Bani; Keatley, Patrick; Huang, Ye; Agbonaye, Osaru; Ademulegun, Oluwasola O.; Hewitt, Neil
Highlights: Evaluation of behind the meter battery storage in a regional hospital. Optimisation of functions and capacity. Participation in ancillary services markets to achieve economic viability. Economic evaluation using simple payback and net present value. New revenue streams for the health sector from battery energy storage systems. Abstract: The ambitious target of reaching net-zero greenhouse gas emissions by 2050 in the UK, which includes the decarbonisation of heat and electricity, means the increase of instantaneous power from non-dispatchable renewable energy sources (RESs). The intermittency of RESs will cause stability issues for the grid resulting from the mismatch between generation from RES and load demand. Battery energy storage systems (BESS) can match loads with generation and can provide flexibility to the grid. This study is proposing the health sector as a new flexibility services provider for the grid through BESS. The health sector has large loads that run throughout the year, and by managing this load it can provide flexibility to the grid.  Four different scenarios have been evaluated for a range of behind-the-meter (BTM) BESS for a hospital in the UK to provide arbitrage and ancillary services considering the option of installing a photovoltaic (PV) system. It was found that BESS would not be economically viable through arbitrage alone since the payback period was always greater than the BESS lifetime. However, bundling services by participating in the ancillary services market resulted in payback periods as low as 3.10 years for some systems, and the net present value (NPV) could reach more than £5 million. This work provides evidence that the health sector can be a significant player in the transition to a renewables-led energy system, an exemplar for other sectors, and one of the solutions to recovery from the COVID19 pandemic. Graphical abstract: Image, graphical abstract